Algoritmos laborales: big data e inteligencia artificial - Toyama Miyagusuku, Jorge (2019)
Technology is constantly evolving and influencing all spheres in our life. Law and, in particular, labour law are not far from the technological revolutions as, increasingly, companies are incorporating algorithms as strategic partners for decision making.In this article, the authors seek to analyze and explain both the impact of the use of logarithms in employment relations, using concepts of big data and artificial intelligence and the protection off ered by labour law against this new trend.